Deskripsi Pemahaman Multirepresentasi Kimia Siswa pada Materi Larutan Elektrolit dan Non Elektrolit - Annisa Elvina; Latisma DJ (Orbital: Jurnal Pendidikan Kimia, 2022)
The material in chemistry subjects can be fully understood if the learning emphasizes the macroscopic, sub-microscopic and symbolic levels and links the three levels. The material for electrolyte and non-electrolyte solutions contains abstract concepts. Students only understand concepts that exist macroscopically and memorize concepts sub-microscopically or symbolically on the material, resulting in students having difficulty understanding the material. This study aims to describe the understanding of students' multi-representation of chemistry on the material of electrolyte and non-electrolyte solutions for class X MAN 2 Kota Padang. The research method used is descriptive quantitative. Samples were taken randomly, namely random sampling for class X IPA 6 as many as 34 samples. The instruments used are descriptive tests and interviews, the questions given include 3 levels of representation using Miles & Huberman data analysis techniques and data processing with Microsoft Excel. The results showed that 53% of students could connect the three levels of chemical representation of 6 questions, 44% of students could connect the three levels with 5 questions out of 6 questions and only 3% of students could connect the three levels with 3 questions out of 6 questions. The average understanding of the highest representation is on macroscopic representation because 98% of the number of students who have a very good understanding category, while at the sub-microscopic level only 9% of the number of students who have very good understanding category, and at the symbolic level 44% of the number of students who have very good understanding category.